2021
DOI: 10.1038/s41598-021-93983-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive exposure assessments from the viewpoint of health in a unique high natural background radiation area, Mamuju, Indonesia

Abstract: Mamuju is one of the regions in Indonesia which retains natural conditions but has relatively high exposure to natural radiation. The goals of the present study were to characterize exposure of the entire Mamuju region as a high natural background radiation area (HNBRA) and to assess the existing exposure as a means for radiation protection of the public and the environment. A cross-sectional study method was used with cluster sampling areas by measuring all parameters that contribute to external and internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…A detailed study on the radiation exposure pathways in that area showed that, to such total effective dose, the radionuclide inhalation ( 222 Rn and 220 Rn isotopes) contributed with 70%, the ambient gamma radiation from radionuclides in the ground contributed with 29%, the cosmic radiation contributed with 0.5%, and the ingestion of local foods and water contributed with 0.5% [ 37 ]. Another study for an HBRA in Mamuju, Indonesia, reported a similar percent contribution of exposure pathways and radon isotopes to the average effective dose for inhabitants, determined at 32 mSv y −1 (range 17–155 mSv y −1 ) [ 88 ]. Detailed studies such as these ones are missing for most of the HBRAs referred above.…”
Section: Resultsmentioning
confidence: 92%
“…A detailed study on the radiation exposure pathways in that area showed that, to such total effective dose, the radionuclide inhalation ( 222 Rn and 220 Rn isotopes) contributed with 70%, the ambient gamma radiation from radionuclides in the ground contributed with 29%, the cosmic radiation contributed with 0.5%, and the ingestion of local foods and water contributed with 0.5% [ 37 ]. Another study for an HBRA in Mamuju, Indonesia, reported a similar percent contribution of exposure pathways and radon isotopes to the average effective dose for inhabitants, determined at 32 mSv y −1 (range 17–155 mSv y −1 ) [ 88 ]. Detailed studies such as these ones are missing for most of the HBRAs referred above.…”
Section: Resultsmentioning
confidence: 92%
“…The IAEA 375 is a homogenized top soil (<20 cm) of 0.3 mm grain size. 30 , 31 The reference material contains the following radionuclides: 40 K, 90 Sr, 106 Ru, 125 Sb, 129 I, 134 Cs, 137 Cs, 226 Ra, 232 Th, 228 Th, 234 U, 238 U, 238 Pu, 239+240 Pu, and 241 Am. 36 , 37 Typically, spectral resolution of about 7.3% full width at half maximum, FWHM at 662 keV of 137 Cs is specified by detector manufacturers.…”
Section: Methodsmentioning
confidence: 99%
“…Often, occurrences of high background radiation have been associated with high radon concentration. 30 , 31 However, a survey of literature revealed there has been no data regarding the radioactivity of the soil in the area and delineation of the activities across the lithologies.…”
Section: Introductionmentioning
confidence: 99%
“…The annual effective dose shown in the previous report was estimated as the accumulation of the dose from external exposure (environmental gamma radiation) and internal exposure (mainly through breathing of indoor radon) based on our previous reports. This radioactivity was mainly derived from uranium ( 238 U), thorium ( 232 Th), radon ( 222 Rn), thoron ( 220 Rn) and their progeny contained in soil [ 5 , 6 ]. However, do the proteomic changes observed in residents living under chronic long-term low-dose radiation exposure also occur with a single acute high-dose radiation exposure, such as a radiation exposure accident?…”
Section: Introductionmentioning
confidence: 99%